Features of the functioning of past tense verbs in «Notes of a Young Doctor» by M.A. Bulgakov (based on the story «Egyptian Darkness») - I.V. Vasilyeva; A.A. Matigorova (Язык и текст)
Context and relevance. The article discusses the problem of structural and semantic analysis of past tense verbs in a literary text. In the field of linguopoetics, the verb becomes the main means of organizing the artistic space. At the present stage of understanding the verb tense category, the issue of its functioning in the text occupies a special place, but this topic has not yet been fully explored. Goal. To identify the main functional aspects of past tense verbs in a literary text. Hypothesis. The linguistic analysis, based on the study of the grammatical and functional-semantic nature of the Russian verb, allows us to penetrate deeper into the fabric of the literary text. Methods and materials. The methodological basis of the research was the work of A.V. Bondarko, V.V. Vinogradov and M.M. Bakhtin. The main research method was the method of structural and semantic description, consisting of observation, generalization, classification of linguistic phenomena. When reviewing the material, the functional-textual approach was taken into account. Results. Based on the position of A. V. Bondarko on the meanings of the specific-temporal forms of the verb was defined and formulated semantically by the «temporal shifts» and the structural aspect of the artistic world in the work of M.A. Bulgakov «Egyptian Darkness». Conclusions. It is shown that the functioning of verb forms plays a key role in the organization of a literary text. It is recommended to include a structural and semantic analysis of the verb forms that make up the literary text in the linguopoetic aspect.